2013
DOI: 10.1371/journal.pone.0055330
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Response of Tribolium castaneum Larvae to Bacillus thuringiensis Toxin Producing Strains

Abstract: Susceptibility of Tribolium castaneum (Tc) larvae was determined against spore-crystal mixtures of five coleopteran specific and one lepidopteran specific Bacillus thuringiensis Cry toxin producing strains and those containing the structurally unrelated Cry3Ba and Cry23Aa/Cry37Aa proteins were found toxic (LC50 values 13.53 and 6.30 µg spore-crystal mixture/µL flour disc, respectively). Using iTRAQ combined with LC-MS/MS allowed the discovery of seven novel differentially expressed proteins in early response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 50 publications
1
39
2
1
Order By: Relevance
“…Btt produces the Cry3Aa toxin, which when applied in its purified form (without the addition of spores), caused mortality to the yellow mealworm beetle Tenebrio molitor but not to T. castaneum [27]. A recent study [41] reported a very low mortality in T. castaneum when exposed to spore-crystal mixtures of Cry3Aa producing strain. The different mortality observed in this study might come from a different bacterial chromosomal background or from differences in spore concentrations that were provided in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Btt produces the Cry3Aa toxin, which when applied in its purified form (without the addition of spores), caused mortality to the yellow mealworm beetle Tenebrio molitor but not to T. castaneum [27]. A recent study [41] reported a very low mortality in T. castaneum when exposed to spore-crystal mixtures of Cry3Aa producing strain. The different mortality observed in this study might come from a different bacterial chromosomal background or from differences in spore concentrations that were provided in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this difference was evident only after 8 hr of plant feeding, suggesting that food intake could play a role in this difference. The immune protein apolipophorin‐III was previously reported to be upregulated in response to Cry3Ba exposure in Tribolium castaneum (Herbst) (Contreras, Rausell, & Real, ,b). However, no apolipophorin was differentially expressed in the present RNA‐seq results.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, CSPs and OBPs are involved in olfaction and chemical communication in insects, but the functions of members of these large families of genes might be diverse [8, 45]. Elevated levels of CSP gene transcripts were previously reported after oral exposure to B. thuringiensis or its toxins in Tenebrio molitor [46] and T. castaneum [16], and a role of OBP-C12 in T. castaneum defense against B. thuringiensis was also demonstrated [16]. The beetle populations differed in the specific sets and the expression dynamics of these genes, some of which were also differentially expressed upon pricking infection.…”
Section: Discussionmentioning
confidence: 99%